Caught between desire and danger: power, agency and emotion work in American college women's heterosexual lives - Cooper, Chiara Elena (The University of Edinburgh, 2021)
This empirical study, grounded in a feminist epistemology, analyses young, American college women’s reflections on their heterosexual lives. The context of these women’s heterosexual experiences provides a backdrop to explore how the phenomena of power, agency, and selfwork emerge through and interplay with heterosexuality. Building on existing research on various aspects of women’s heterosexual lives (Fine, 1988; Holland et al, 1998; Tolman, 2002; Jackson and Cram, 2003; Powell, 2010; Beres and Farvid, 2010; Wade, 2017; Pickens and Braun, 2018), this study examines the ways that young women adhere to restrictive ideologies which dictate rules as to how to be a traditionally feminine woman and how heterosex ought to be experienced; but also how their accounts are able to, temporarily, rupture these oppressive power structures, as the women critically consider their capacity for agency and freedom. The study is based on 5 focus group interviews with 18 women at a large, southern public university in the United States. This thesis explores how nuances of pleasure and danger as well as agency and structure transpire through the young women’s narratives of heterosexuality, building up a complex picture of their experiences. In extending a Foucauldian (1978, 1980) understanding of discourse and power, this study will argue that the young women still have to navigate pervasive heterosexual discourses which dictate appropriate heterosexual behaviour. At the same time, this thesis critically analyses the women’s claims to sexual empowerment and agency – which suggest there is some room for circumventing these discourses albeit only briefly – from a feminist perspective. Finally, this research draws on Hochschild’s (1979, 1983) conceptualisation of emotional labour to argue that the young women engage in a form of emotional labour, or emotion work, in order to maintain their heterosexual relationships and their emotions (and those of others) and to manage certain sexual situations, including those involving questions of risk and safety. Thus, this thesis addresses two interrelated problems that are prominent in the literature: the first is that feminist theory aims to provide women the conceptual tools to understand their heterosexual lives, but often either reduces their experiences to structural oppression or a vague liberal view of empowerment. Neither of these fully grapple with the challenges and opportunities for change that women face in heterosexual encounters. Secondly, the women interviewed often rely on strategies based on linguistic interactions and emotion work to manage their heterosexual relationships and a coherent sense of self. Women’s heterosexuality as explored in this thesis is considered a complex contradiction; the study concludes that young women are, on the one hand, able to articulate their sexual desires in an individualised sense but that acting out these pleasures with a partner proves difficult, suggesting that progress of sexual freedom remains intertwined with the intricate constraints of old.